Human Flicker Fusion Correlates With Physiological Measures of Magnocellular Neural Efficiency - Brown, Alyse; Corner, Molly; Crewther, David P.; Crewther, Sheila G. (Frontiers in Human Neuroscience, 2018)
The rapidity with which the visual system can recover from stimulation in order to respond again has important implications for efficiently processing environmental stimuli in real time. To date, there has been little integration of the human psychophysical and physiological research underlying the neural mechanisms contributing to temporal limits on human visual perception. Hence, we investigated the relationship between achromatic flicker fusion frequency and temporal analysis of the magnocellular (M) and parvocellular (P) contributions to the achromatic nonlinear multifocal Visual Evoked Potential (mfVEP) responses recorded from occipital scalp (Oz). It was hypothesized, on the basis of higher temporal cut-off frequencies reported for primate M versus P neurons, that sinusoidal flicker fusion frequencies would negatively correlate with the amplitude of M- but not P-generated nonlinearities of the mfVEP. This hypothesis was borne out in 72 typically developing young adults using a 4-way forced choice sinusoidal flicker fusion task: amplitudes of all nonlinearities that demonstrated a clear M-generated component correlated negatively with flicker thresholds. The strongest of these correlations were demonstrated by the main M nonlinearity component (K2.1N70-P100) for both high contrast (r= -.415, n=64, p< .0005) and low contrast (r= -.345 n=63, p< .002) conditions, indicating that higher achromatic flicker fusion threshold is linked to a more efficient (smaller second order kernels) M system. None of the peaks related to P activity showed significant correlations. These results establish flicker thresholds as a functional correlate of M-pathway function as can be observed in the nonlinear analysis of mfVEP.